The neurophysiology of the esophagus. (11th October 2013) - Woodland, Philip; Sifrim, Daniel; Krarup, Anne Lund; Brock, Christina; Frøkjær, Jens Brøndum; Lottrup, Christian; Drewes, Asbjørn Mohr; Swanstrom, Lee L.; Farmer, Adam D.
Abstract : This paper reports on the neurophysiology of the esophagus, including on the uneven distribution of innervation in the esophagus, reflected by the increased sensitivity and perception of gastroesophageal reflux disease (GERD) events in the proximal rather than distal esophagus; the role of the enteric nervous system (ENS) in swallowing; the role of the physiological stress‐responsive systems, including the autonomic nervous system (ANS) and the hypothalamic–pituitary–adrenal (HPA) axis in mediating esophageal pain; the advances in understanding pain mechanisms and brain structure provided by technological imaging advances; investigations into the efficacy of the descending‐pain control system, including diffuse noxious inhibitory control (DNIC); the role of abnormal nervous signaling in afferent pathways in the pathogenesis of Barrett's esophagus (BE); and the contribution of the esophageal mucosa to reflux symptoms.